2020
DOI: 10.1136/jitc-2020-000552
|View full text |Cite
|
Sign up to set email alerts
|

LAG3(LAG-3,CD223) DNA methylation correlates with LAG3 expression by tumor and immune cells, immune cell infiltration, and overall survival in clear cell renal cell carcinoma

Abstract: BackgroundLymphocyte activating 3 (LAG3, LAG-3, CD223) is a promising target for immune checkpoint inhibition in clear cell renal cell carcinoma (KIRC). The aim of this study was to investigate the epigenetic regulation ofLAG3in KIRC by methylation.MethodsWe correlated quantitativeLAG3methylation levels with transcriptional activity, immune cell infiltration, and overall survival in a cohort of n=533 patients with KIRC and n=160 normal adjacent tissue (NAT) samples obtained from The Cancer Genome Atlas (TCGA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 48 publications
2
70
0
Order By: Relevance
“…Interestingly, the inverse correlation between LAG3 and T-bet is bidirectionally causal (i.e., deletion of either T-bet or LAG3 increases the expression of the other) on murine T cells, suggesting that LAG3 promotes exhaustion and vice-versa ( 7 , 22 , 23 ). Methylation, particularly of the LAG3 promoter, appears to tightly regulate LAG3 expression ( 24 , 25 ).…”
Section: Expressionmentioning
confidence: 99%
“…Interestingly, the inverse correlation between LAG3 and T-bet is bidirectionally causal (i.e., deletion of either T-bet or LAG3 increases the expression of the other) on murine T cells, suggesting that LAG3 promotes exhaustion and vice-versa ( 7 , 22 , 23 ). Methylation, particularly of the LAG3 promoter, appears to tightly regulate LAG3 expression ( 24 , 25 ).…”
Section: Expressionmentioning
confidence: 99%
“…Furthermore, the role of LAG3 methylation in melanoma cells needs further evaluation. Recently, LAG3 expression in clear cell renal carcinoma cell lines and a tumor cell-intrinsic LAG3 protein expression was reported [9] . However, knowledge of tumor cell-intrinsic expression of the LAG3 protein in melanoma is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…in melanoma and colorectal carcinoma [8] . In addition, a recent report suggests a LAG3 expression by tumor cells as shown in clear cell renal cell carcinomas [9] .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Of particular note is the 24 connected group of T cell regulatory genes PDL1, CD80, LAG3, HAVRC2, and IL10. LAG3 has 25 been shown to be of importance in immune infiltration and overall survival in renal cell 26 carcinoma (Klümper et al, 2020), acts as an important player in intratumoral T cell exhaustion in 1 lymphoma (Yang et al, 2017), and has been suggested as a potential therapeutic target for new 2 ICB strategies (Long et al, 2018). HAVRC2 (also known as TIM3) has been shown to be an 3 important inhibitory T cell receptor, as well as a defining characteristic of exhausted T cells in 4 concert with PD1 (Lee et al, 2016), (Wolf et al, 2020).…”
Section: Pdl1 5mentioning
confidence: 99%